Cataloging Existing Hearing Loss Cohort Data to Guide the Development of Precision Medicine for Sensorineural Hearing Loss: A Systematic Review of Hearing Repositories - Sethukumar, Priya; Mandavia, Rishi; Yildirim, Omursen; Hazell, Georgina; Devakumar, Haran; Ahmed, Muhammad; Stragier, Emilien; Duran, Marie Josée; Schilder, Anne G.M.; Mehta, Nishchay (Journal of International Advanced Otology, 2023)
Recent breakthroughs in our understanding of sensorineural hearing loss etiology have encouraged the identification of novel hearing therapeutics, paving the way for precision hearing medicine. Critical to this field is the curation of health resources on hearing data. A systematic review of the literature was conducted to map existing (inter)national and regional datasets that include hearing data to inform the development of future hearing repositories. Systematic literature review was performed adhering to Preferred Reporting Items for Systematic Review and MetaAnalysis recommendations. Databases, including those from gray literature, were searched to identify publications reporting on phenotypic and/ or genotypic hearing data in May 2019. The databases reviewed were Medline, PubMed, Embase databases, and Google Scholar. Publications on local datasets were excluded. All hearing datasets identified in the screening process were noted. For each dataset, geography, context, objective, period of time run, numbers and demographics of participants, genomic data, hearing measures and instruments used were extracted and cataloged. One hundred and eighty-eight datasets were identified, containing hearing data on populations ranging from 100 to 1.39 million individuals, and all extracted data have been cataloged. This searchable resource has been made accessible online. This unique catalog provides an overview of existing datasets that contain valuable information on hearing. This can be used to inform the development of national and international patient data repositories for hearing loss and guide strategic collaboration between key stakeholder groups, pivotal to the delivery and development of sensorineural hearing loss precision diagnostics and treatments. Cite this article as: Sethukumar P, Mandavia R, Yildirim O, et  al. Cataloging existing hearing loss cohort data to guide the development of precision medicine for sensorineural hearing loss: A systematic review of hearing repositories. J Int Adv Otol. 2023;19(5):420-425.